SOCIAL ANXIETY IN ADOLESCENTS: PREVALANCE AND MORBIDITY - Zaqia Bano (Army Medical College Rawalpindi, 2019)
Objective: To explore the prevalence of “social anxiety” among adolescent student of Pakistani students.